Predictors of the prevalence of bacterial STI among young disadvantaged Indigenous people in north Queensland, Australia. Issue 4 (5th August 2003) - Miller, G C; McDermott, R; McCulloch, B; Fairley, C K; Muller, R
Abstract : Objective: To identify sexually transmitted infections in rural and remote Indigenous communities in north eastern Australia and examine factors that may influence prevalence. Methods: A cross sectional survey of 26 Aboriginal and Torres Strait Islander communities in northern Queensland was carried out. 3313 people (2862 Indigenous) aged 15 years and over resident in participating communities during the period March 1998 to December 2000. The main outcome measures were community and population prevalence of chlamydia and gonorrhoea and independently associated risk factors. Results: A total of 238 cases of chlamydia, 66 cases of gonorrhoea, and 37 cases of co-infection were detected among Indigenous participants. Prevalence of chlamydia and/or gonorrhoea ranged from 23.0% among 15–19 year olds to 3.5% among those 40 years and older. In the adjusted analysis younger age, female sex, lower socioeconomic status, the use of alcohol and tobacco, and the structure of community health services were independently associated with a higher prevalence of bacterial STI. Conclusion: This study highlights the need for improved STI control in north Queensland Indigenous communities through strategies to improve the reach and accessibility of primary healthcare services.